SCHOOL OF FORMALISTS - Mizrabova Jeren Ismailovna (Ta'lim innovatsiyasi va integratsiyasi, 2026)
Abstract: This article provides a theoretical overview of Formalism as a school of twentieth-century literary criticism focused on the analysis of the internal structure of the literary text. It examines the key principles of Russian Formalism and Anglo-American New Criticism, including the understanding of literature as an autonomous system,  the  priority  of  formal  linguistic  elements,  and  the  concept  of  literariness. Special  attention  is  given  to  V.  Shklovsky’s  idea  of  “defamiliarization”  and  the distinction between fabula and syuzhet, as well as R. Jakobson’s contribution to the development of Structuralism through his theory of metaphor and metonymy and the concept of the poetic function of language.